Differences Between Posttraumatic Growth and Resiliency: Their Distinctive Relationships With Empathy and Emotion Recognition Ability - Elam, Taylor; Taku, Kanako (Frontiers in Psychology, 2022)
Posttraumatic growth (PTG) and resiliency have been observed among people who experienced life crises. Given that the direct relationships between PTG and resiliency have been equivocal, it is important to know how they are different in conjunction with cognitive ability. The purpose of this study is to examine how perceived PTG and resiliency would be respectively associated with empathy and emotion recognition ability. A total of 420 college students participated in an online survey requiring them to identify emotions based on photographs of facial expressions, report their traumatic experiences, and respond to the PTG Inventory, Brief Resilience Scale, and Questionnaire of Emotional Empathy. The results suggest that perceived PTG was not associated with empathy but significantly predicted increased emotion recognition, whereas resiliency showed a negative relationship with empathy but no significant relationship with emotion recognition. These findings demonstrate that self-perceived PTG may be associated with cognitive ability, which could be due to one’s growth within relationships and social interactions. Even though growing after trauma may promote resilient characteristics, the current results indicate that PTG and resiliency may foster different outcomes. Since empathy and emotion recognition are affected by other contextual factors, future studies should assess how empathy and the type of errors in emotion recognition may be associated with situational factors that are beyond personal factors such as post-traumatic life experiences or personality.